Cork-like filaments for Additive Manufacturing - Silva, S.P. Magalhães da (2020)
A cork-like filament fully biodegradable and filled with low granulometry cork powder residues was developed. Cork-polymer composites (CPC) were prepared using a Brabender type mixer incorporating 15% (w/w) of cork powder (corresponding to 55% (v/v)) and having polylactic acid (PLA) as matrix. In order to promote a chemical adhesion between cork particles and PLA, the effect of maleic anhydride grafted PLA (MAgPLA) was studied. Fourier Transform Infrared – Attenuated Total Reflection (FTIR-ATR) analysis was used to evaluate the func- tionalization of MAgPLA onto the polymeric chain. The addition of MAgPLA enhanced the mechanical behavior by increasing tensile properties while improving the dispersion of cork particles within PLA matrix. In addition, cork particles and MAgPLA acted as nucleating agents during PLA melting process. To evaluate the printability of the developed CPC filament, specimens were printed by Fused Filament Fabrication (FFF) and compared to those obtained by injection molding (IM). FFF allowed to preserve the cork alveolar structure in the specimens, benefiting CPC mechanical behavior. 3D parts could be printed with the CPC filament thereby demonstrating the usefulness of the fully biodegradable cork-based filament here developed. 3D printed parts exhibit unique characteristics, such as a nonplastic and warm touch, a natural colour and the release of a pleasant odour during the printing process.